ANALISIS PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL COOPERATIVE PROBLEM BASED LEARNING (CPBL) TERINTEGRASI BAHAN AJAR KIMIA SMA/MA - Uswatun Hasanah. S; Rachmat Rizaldi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This research is an experimental study that aims to determine the analysis of learning outcomes among students who are taught using the Cooperative Problem Based Learning (CPBL) model integrated with SMA/MA chemistry teaching materials that have been developed with student learning outcomes that are taught using the Cooperative Problem Based Learning model (CPBL) integrated with SMA/MA chemistry teaching materials at schools. The population in this study were all students of class X SMA/MA in Pekanbaru City and Kampar Regency, Riau. The sampling technique was purposive sampling. The research sample consisted of 2 classes, namely the experimental class 1 taught using the integrated Cooperative Problem Based Learning (CPBL) model of SMA/MA chemistry teaching materials that had been developed and in experiment class 2 it was learned using the Cooperative Problem Based Learning (CPBL) model integrated with SMA/MA chemistry teaching materials at school. The research instrument was an objective test of learning outcomes with a pretest and posttest design. The data analysis starts from the results of the requirements test in the form of a normality test and a homogeneity test. The results show that the data are normally distributed and have the same variance. The next data analysis technique was carried out by using the Independent Sample T-test on the SPSS 16 for windows program with a significant level of 0.05. The results showed that Ha1 was accepted at a sig. 0.000<0.05.